Thiol-Functionalized Mesoporous Carbons as Adsorbents of Heavy-Metal Ions - Katarzyna Michalak-Zwierz; Karolina Gdula; Katarzyna Tyszczuk-Rotko; Witold Zawadzki; Andrzej Dąbrowski; Mariusz Barczak (Adsorption Science & Technology)
Ordered mesoporous carbon has been obtained by hard templating using SBA-15 and subsequently, oxidized (by treatment with ammonium persulphate) and thiol-functionalized (by treatment with thiol-contained polyhedral oligomeric silsesquioxane). Pristine and thiol-functionalized carbons were characterized by nitrogen adsorption, X-ray diffractometry, X-ray photoelectron spectroscopy, scanning electron microscopy and transmission electron microscopy and tested for their ability to adsorb bivalent heavy-metal ions (Cd, Cu, Pb, Zn) from the aqueous solutions. The observed static adsorption capacities are very high up to 0.76 mmol/g. Adsorption kinetics is also very fast: approximately 90% of the equilibrium amount is adsorbed after several minutes.